2001
DOI: 10.1128/iai.69.11.7074-7082.2001
|View full text |Cite
|
Sign up to set email alerts
|

agrExpression Precedes Escape of InternalizedStaphylococcus aureusfrom the Host Endosome

Abstract: Staphylococcus aureus is a versatile pathogen capable of causing life-threatening infections. Many of its cell wall and exoproduct virulence determinants are controlled via the accessory gene regulator (agr). Although considered primarily as an extracellular pathogen, it is now recognized that S. aureus can be internalized by epithelial and endothelial cells. Traditional experimental approaches to investigate bacterial internalization are extremely time-consuming and notoriously irreproducible. We present here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
170
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(177 citation statements)
references
References 43 publications
(30 reference statements)
7
170
0
Order By: Relevance
“…Host microenvironments could potentiate quorum sensing either by increasing the concentration of the autoinducer, as we showed with clumping, or by limiting diffusion of the autoinducer, as may occur within an intracellular vacuole (39). Thus, virulence as a quorum sensingregulated behavior may not represent exclusively the absolute bacterial number but, rather, the microenvironment in the host surrounding the bacteria.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Host microenvironments could potentiate quorum sensing either by increasing the concentration of the autoinducer, as we showed with clumping, or by limiting diffusion of the autoinducer, as may occur within an intracellular vacuole (39). Thus, virulence as a quorum sensingregulated behavior may not represent exclusively the absolute bacterial number but, rather, the microenvironment in the host surrounding the bacteria.…”
Section: Discussionmentioning
confidence: 87%
“…While agr-deficient bacteria are less virulent than WT (1, 24), they can cause serious infection and death when given at increased inocula (39,32,40). Therefore, we measured both morbidity and mortality in mice infected with an appropriate challenge dose of agr-deficient bacteria and found that fibrinogen depletion affected neither morbidity (Fig.…”
Section: Fibrinogen Depletion Prevents Morbidity and Mortality After mentioning
confidence: 99%
“…To overcome these problems, translational signals optimized for Gram-positive bacteria have been introduced in front of luxA, luxC and luxE resulting in enhanced expression in Staphylococcus aureus. 47 The same construct has been successfully used for bioluminescent labelling of Listeria monocytogenes, 48,49 Streptococcus pneumoniae, 50 Bifidobacterium breve 51,52 and Mycobacterium tuberculosis and M. smegmatis. 53 A similar approach, however introducing Gram-positive ribosome binding sites in front of all genes of the luxABCDE operon has been applied by others.…”
Section: 79mentioning
confidence: 99%
“…61 A promoter fusion to an optimized P. luminescens lux operon was used to measure expression of a peptide sensing system of S. aureus in response to the signalling peptide in vitro and during phagocytosis and intracellular growth in macrophages. 47 The same system was used to quantify activities of various promoters of L. monocytogenes during growth in batch culture, infection of epithelial cells in vitro and in organs of infected mice ex vivo 48,49,[62][63][64] (Fig. 3).…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…Recently a gfp-luxABCDE reporter construct, under the control of the XylA promoter, was used to monitor the expression and temporal induction of the quorum-sensing accessory gene regulator (agr) in S. aureus infecting bovine mammary epithelial MAC-T cells (133). The reporter gene expression was occasioned by the virulence factor-mediated escape of S. aureus from the host endosome and its ensuing intracytoplasmic growth.…”
Section: Imaging Eukaryotic Luciferase Expression In Cells and Cell Cmentioning
confidence: 99%